Ұлттық күйініштің лебі - Рахманова, Н.М. (ҚарМУ баспасы, 2010)
В статье рассматриваются особенности идейно-тематического и художественно-эстетического содер- жания романа М.Ауэзова «Лихая година» и проблемы его публикации. Проанализированы литературоведческие работы Ш.Айтматова, Э.Шарипова, Г.Мусрепова и Р.Нургали об исторической ценности романа. Автором также прослеживается возникновение сюжета и исследуются художест- венные особенности создания образов романа. The article is devoted to the features of the ideologically-thematic and art-aesthetic maintenance of the M.Auezov’s novel «The Hard Time» and problems of its publication are considered. S.Ajtmatov, E.Sharipov, G.Musrepov, and R.Nurgali’s works in revealing a historical value of the novel are analyzed. An object of research also becomes to research of occurrence of a plot and art features of creation of images of the novel.
Keywords: М. Әуезов; "Қилы заман" романы; романның көркем-эстетикалық шығармармашылығы; көркемдік ерекшелігін зерттеу; көркемдік шығармашылық ерекшелігі